Cisco ASA and PIX firewall handbook - Hucaby, Dave (Cisco Press networking technology series., 2005)
The complete guide to the most popular Cisco PIX®, ASA, FWSM, and IOS® firewall security features Learn about the various firewall models, user interfaces, feature sets, and configuration methods Understand how a Cisco firewall inspects traffic Configure firewall interfaces, routing, IP addressing services, and IP multicast support Maintain security contexts and Flash and configuration files, manage users, and monitor firewalls with SNMP Authenticate, authorize, and maintain accounting records for firewall users Control access through the firewall by implementing transparent and routed firewall modes, address translation, traffic filtering, user authentication, content filtering, application inspection, and traffic shunning Increase firewall availability with firewall failover operation Understand how firewall load balancing works Generate firewall activity logs and learn how to analyze the contents of the log Verify firewall operation and connectivity and observe data passing through a firewall Control access and manage activity on the Cisco IOS firewall Configure a Cisco firewall to act as an IDS sensor Every organization has data, facilities, and workflow processes that are critical to their success. As more organizations make greater use of the Internet, defending against network attacks becomes crucial for businesses. Productivity gains and returns on company investments are at risk if the network is not properly defended. Firewalls have emerged as the essential foundation component in any network security architecture. Cisco ASA and PIX Firewall Handbook is a guide for the most commonly implemented features of the popular Cisco Systems® firewall security solutions. This is the first book to cover the revolutionary Cisco ASA and PIX® version 7 security appliances. This book will help you quickly and easily configure, integrate, and manage the entire suite of Cisco® firewall products, including Cisco ASA, PIX version 7 and 6.3, the Cisco IOS router firewall, and the Catalyst Firewall Services Module (FWSM). Organized by families of features, this book helps you get up to speed quickly and efficiently on topics such as file management, building connectivity, controlling access, firewall management, increasing availability with failover, load balancing, logging, and verifying operation. Shaded thumbtabs mark each section for quick reference and each section provides information in a concise format, with background, configuration, and example...